The Traditional Fishery on Deh Cho: An Ethnohistoric and Archaeological Perspective - Hanks, Christopher C.; Winter, Barbara J. (ARCTIC, 1991)
Dene use of the resources of Deh Cho, the preferred Slavey name for the Mackenzie River, in the late pre-contact and early post-contact periods is not well understood. This paper examines the archaeological record of the Mackenzie Valley in relation to a model of Native use of the river, based upon Alexander Mackenzie's observations on the exploitation of the fishery at the first direct contact between Europeans and the Dene along Deh Cho. Use of archaeological data, ethnographic analogy and later historic sources provokes the conclusion that Dene land and river resource use did not drastically change as a result of European contact and the fur trade.Key words: Slavey, Dogrib, Hare, Dene, Athapaskan, fish, Mackenzie River, traditional harvesting, ethnoarchaeology, ethnohistory Mots clés: Slavey, Dogrib, Hare, Déné, Athapaskan, poisson, fleuve Mackenzie, collecte traditionnelle pour la subsistance, ethnoarchéologie, ethnohistoire